Homo inc.orporated : le triangle et la licorne qui pète - Bourcier, Sam (M.H) (Cambourakis, 2017)
Avec Homo Inc.orporated, Sam Bourcier poursuit la réflexion menée dans la trilogie des Queer Zones. Mariage, procréation, travail, patrie, les gais et les lesbiennes ont basculé dans la sphère de la reproduction et de la production. Que reste-t-il du sujet politique LGBT lorsqu'il est défini par le droit et le management de la diversité ? Pas grand-chose. Raison pour laquelle les queers et les transféministes se mobilisent pour un agenda de redistribution économique et de justice sociale plus large que la simple demande d'égalité et d'intégration. Homo Inc.orporated propose une critique radicale de l'homonationalisme et des politiques de l'égalité des droits. C'est aussi une boîte à outils pour lutter contre le néolibéralisme, avec une réflexion et de nouveaux moyens d'action sur les politiques du savoir à l'université, le genre comme travail, la grève du genre sans oublier le gender fucking !
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; cours; europe; fem1000; france; identités LGBTQIA2+; justice sociale; militance; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; thématiques; transféminisme

« Queer », « transpédégouine », « torduEs », entre adaptation et réappropriation, les dynamiques de traduction au cœur des créations langagières de l’activisme féministe queer - Lorenzi, Marie-Émilie (GLAD!Revue sur le langage, le genre et les sexualités, 2017)
S’il ne fait aucun doute que les activistes féministes queer ont pu reprendre à leur compte le slogan « mon corps est un champ de bataille », elles et ils n’en ont pas pour autant négligé d’investir le langage, ce champ de bataille symbolique. Intervenir sur la langue, se réapproprier les discours de haine en les détournant, sont alors autant de stratégies contre-discursives participant activement au processus de subjectivation. Les enjeux de langage deviennent ainsi un terrain propice pour appréhender le monde, élaborer un espace commun, intelligible et safe, et se constituer en tant que sujet. Ils participent pleinement à l’élaboration politique, identitaire et culturelle de la mouvance ou praxis féministe queer en France. Cette analyse cherche à examiner les dynamiques de traduction au cœur des créations langagières des activistes féministes queer, notamment celles qui relèvent des questions d’autodéfinition. Bien plus qu’une simple formalité de transcription langagière, la traduction soulève des enjeux politiques et culturels déterminants. À partir d’une lecture contextualisée et au plus près des usages, il s’agit ici de souligner l’ambivalence et la complexité de tout processus de traduction, oscillant entre circulation et déformation, réappropriation et reconfiguration.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; communication inclusive; cours; discipline; europe; fem1000; france; identités LGBTQIA2+; langage; pratiques féministes; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; thématiques; traduction

A messy trajectory: From medical sociology to crip theory - Egner J. (Research in Social Science and Disability ; 9, 2016)
Purpose The purpose of this paper is to draw attention to the work of sociologists who laid the foundation for queer and crip approaches to disability and to address how queer and crip theory has and can help to re-conceptualize our understandings of health, illness, disability, and sexuality. Methodology/approach This paper is an examination of historical moments and prominent literature within medical sociology and sociology of disability. Sociological and popular understandings of disability and sexuality have often mirrored each other historically. Although this literature review focuses primarily on medical sociology and disability studies literature, some works of scholars specializing in gender studies, sexuality, literature, history, and queer studies are also included Findings In this paper, I argue that the medicalization and pathologization of human differences specifically as it pertains to sexuality and disability within the medical sociological literature have led to constructionist, social model, and feminist critiques. It is these critiques that then laid the foundation for the development of queer and crip theoretical approaches to both disability and sexuality. Originality/value Crip and queer approaches to disability provide a clear call for future sociological research. Few social science scholars have applied queer and crip approaches in empirical studies on disability. The majority of work in this area is located in the humanities and concerned with literary criticism. A broader array of empirical work on the intersection of sexuality and disability from queer/crip perspectives is needed both to refine these postmodern theoretical models and to examine their implications for the complex lived experience that lies at the intersection of sexuality and disability. In queering disability and cripping sexuality and gender, we may be able not only to more fully conceptualize disability, sexuality, and gender as individual social categories, but also to more fully understand the complex intersection of these social locations.
Keywords: EDI; approches et analyses; care; cours; crip; discipline; histoire et politique; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sociologie; sofia; thématiques

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

Beyond the birds and the bees: A study of comprehensive sex education in Oregon high shools - Wicks, Katie J. (Oregon State University, 2014)
Oregon high schools are required to provide comprehensive sex education to students, but there is anecdotal evidence that this is not consistently being carried out across all schools. Despite the significant amount of literature that exists on the topic of sex education, there is a gap in regards to what is being done in Oregon on the application of the sex education policy in schools and on what students want to learn in high school sex education programs. This study is intended to fill that gap in order to enhance the knowledge pool pertaining to the sex education needs of high school students in Oregon. An anonymous online survey was conducted of first-year Oregon State University students between the ages of 18-20. Upon reviewing the results it appears that Oregon’s sex education policy is being carried out in schools, but perhaps not as completely as it should be. It also appears that there is a discrepancy between what students are being taught and what they feel is important to be taught. In doing this research it has become clear that in order to best meet the needs of youth, sex education programs in Oregon high schools need to be more comprehensive and inclusive.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; LGBTQIA2+; amériques; approches et analyses; identités LGBTQIA2+; inclusion; intersectionnalité; mémoires/thèses; oregon; périodes historiques; queer; ressource en ligne; régions géographiques; sexualité; thématiques; école secondaire; éducation sexuelle